Strategi Peningkatan Kesadaran dan Motivasi Masyarakat untuk menjadi Donatur LAZIS: Studi Kasus di Lembaga Zakat Infak dan Sedekah Muhammadiyah - Oktavia, Novi Tri; Sujianto, Agus Eko; Nurohman, Dede; Nurhayati, Dwi Astuti Wahyu (STAI Auliaurrasyidin Tembilahan, 2024)
The aim of this research is to increase people's motivation to become LAZIS donors, especially LAZISMU. Qualitative research method with case study research using the help of NVivo data analysis. The results showed that the efforts of LAZISMU Tulungagung to increase Muslim awareness in ZIS through the distribution of brochures, installation of flayers in several places, and digital boxes on infak boxes in coffee shops or cafes which the QR code is attached to the media. To facilitate muzakki who want to make zakat payments during the month of Ramadan, LAZISMU Tulungagung opened outlets in several mosques in the Tulungagung Regency area. Until now, LAZISMU Tulungagung is still constrained in socialization and awareness ofthe importance of conducting zakat; and the low motivation of being LAZIS donors. Evaluation which was carried out by LAZISMU Tulungagung by delivering whatsapp blasts related to collection, programs, or words of encouragement to pay zakat and infaq through whatsapp blast messages that donors or muzakki can submit a review of the services provided by LAZISMU Tulungagung.